(untitled) (Medical Forum Monthly, 2022)
Objective: To explore the anthropometric measurements, body composition, individual and total antioxidant capacity in prediabetic Pakistani population with and without family history of diabetes. Study Design: Experimental study Place and Duration of Study: This study was conducted at the department of Physiology, Institute of Basic Medical Sciences, Khyber Medical University, Peshawar, Pakistan between February 2019 to January 2020. Materials and Methods: Prediabetics (n=50), 18 to 35years age group, were included in the study, 25 participants in positive and negative family history of diabetes. All those participants with HbA1c in the limit of 5.7– 6.4%, and fasting blood glucose (FBG) between 100 to 126 mg/dL were included the study. The anthropometric measurements including body weight, height, waist and hip circumference, waist hip ratio, BMI, fat mass and body fat% were measured. The fasting blood samples were examined for total and individual antioxidant capacity by sandwich Enzyme Linked Immunosorbent Assay (ELISA). Results: The weight, waist and hip circumference, waist/hip ratio, body mass index, fat mass and body fat% were different in family history positive and negative groups. The mean levels of superoxide dismutase, glutathione peroxidase, Uric acid (p < 0.006), Vitamin C, nitric oxide (p = 0.022) and total antioxidant capacity were higher in negative compared to positive family history group. Conclusion: The anthropometric measurements, individual and total antioxidant capacity were different in prediabetic population with positive and negative family history of diabetes.